Transmembrane helices in “classical” nuclear reproductive steroid receptors: a perspective - Morrill, Gene A. (Nucl Recept Signal, 2015)
Abstract Steroid receptors of the nuclear receptor superfamily are proposed to be either: 1) located in the cytosol and moved to the cell nucleus upon activation, 2) tethered to the inside of the plasma membrane, or 3) retained in the nucleus until free steroid hormone enters and activates specific receptors. Using computational methods to analyze peptide receptor topology, we find that the “classical” nuclear receptors for progesterone (PRB/PGR), androgen (ARB/AR) and estrogen (ER1/ESR1) contain two transmembrane helices (TMH) within their ligand-binding domains (LBD).The MEMSAT-SVM algorithm indicates that ARB and ER2 (but not PRB or ER1) contain a pore-lining (channel-forming) region which may merge with other pore-lining regions to form a membrane channel. ER2 lacks a TMH, but contains a single pore-lining region. The MemBrain algorithm predicts that PRB, ARB and ER1 each contain one TMH plus a half TMH separated by 51 amino acids.ER2 contains two half helices. The TM-2 helices of ARB, ER1 and ER2 each contain 9-13 amino acid motifs reported to translocate the receptor to the plasma membrane, as well as cysteine palmitoylation sites. PoreWalker analysis of X-ray crystallographic data identifies a pore or channel within the LBDs of ARB and ER1 and predicts that 70 and 72 residues are pore-lining residues, respectively. The data suggest that (except for ER2), cytosolic receptors become anchored to the plasma membrane following synthesis. Half-helices and pore-lining regions in turn form functional ion channels and/or facilitate passive steroid uptake into the cell. In perspective, steroid-dependent insertion of “classical” receptors containing pore-lining regions into the plasma membrane may regulate permeability to ions such as Ca(2+), Na(+) or K(+), as well as facilitate steroid translocation into the nucleus.